Topographic effect on the phenology of Ficus pedunculosa var. mearnsii (Mearns fig) in its northern boundary distribution, Taiwan - Kuo, Chu-Chia (Sci Rep, 2017)
Mearns fig grows at the edge of coastal vegetation on uplifted coral reefs, its population and mutualistic-pollinators are susceptible to the influence of extreme weather. To determine the phenology of Mearns fig and the effects of various weather events under small-scale topographic differences, phenology was conducted for 3 years and 7 months. Results showed that Mearns figs had multiple leaf and fig productions year-round. Topographic effects caused population in Frog Rock Trail and Jialeshuei, which are less than 10 km away from each other, to exhibit different phenological patterns after experiencing severe weather events. Northeast monsoons led the Jialeshuei population to show low amounts of leaves and figs in winter and the phenological production was also susceptible to disturbances by typhoons in summer. Fig reproduction in such environment was disadvantageous to maintain pollinators. Besides, topographic complex in microhabitat of Frog Rock Trail protected some individuals from these same events thus safeguard population’s survival. The phenology of Mearns fig would respond to the weather events sensitively, which serve as references for estimating the mutualism system, and as indicators of climate change.